A REVIEW OF EFFECTIVENESS AND SAFETY OF SELECTED BIOLOGICS IN THE TREATMENT OF RHEUMATOID ARTHRITIS - Kariuki, Stephen Mwaura; E.K, Kemoi; Musyoki, Stanslaus Kiilu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Background: Rheumatoid arthritis (RA) is an autoimmune disease that causes disability topatients in the long run. The bone and cartilage degradation are driven by pro-inflammatorycytokines like tumour necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) among others.The traditional treatment for RA is disease modifying anti-rheumatic drugs (DMARDs)despite the serious adverse effects. In the last past few years biologics have been added toDMARDs or replaced them altogether in the treatment of RA. There is however, growingconcern on the effectiveness and safety of these biologics.Aim: This article reviewed the use of Rituximab, Adalimumab, and Golimumab, as well asdnaJP1 peptide and Folate-targeted immunotherapy data to assess their effectiveness andsafety in the treatment of RA.Methods: Data from clinical trials and other animal model experiments published in peerreviewed journal articles were reviewed to determine the effectiveness and safely levels ofthese biologics as used in the treatment of rheumatoid arthritis.Results: We found that combination therapy of biologics and DMARDs has proven effectivein the treatment of RA especially where the latter have failed to reduce disease activity inpatients. Rituximab has been found effective where monotherapy treatment with DMARDsand anti-TNFs have failed.Conclusion: All biologics are generally effective and safe for use in the treatment of RA withminimal side effects being reported.